Water policy and regional economic development: evidence from Henan province, China - Hefei Bai (IWA Publishing, 2021)
With the rapid advance of industrialization and urbanization and the intensified impact of global climate change, the contradiction between the global water shortage and economic growth has become prominent. This paper, taking Henan province as an example, analyzed the influence of water resource policy on regional economic growth through a calculable general equilibrium model and further discussed the relevant policy recommendations. The results showed that the improvement of water supply, water efficiency and water technology could promote the growth of the regional economy and result in a positive effect on regional GDP, employment and resident income. However, the rise of water price has a negative impact on regional economic development, mainly reflected in regional GDP, employment and household income. The improvement of water price, water efficiency and water conservancy technology would lead to a decrease in regional water consumption, while only the increase of the water supply would lead to an increase in water consumption. Accordingly, the paper puts forward policy suggestions, such as accelerating the improvement of water conservancy facilities, establishing a reasonable water price mechanism and actively exploring experience in water conservation and emission reduction. Highlights The quantitative analysis method is used to simulate the impact of four policy changes of water supply, water price, water-use efficiency and water conservancy technology on the main regional economic indicators.; The aim of this move is to reflect the effect and potential impact of future policy changes and put forward policy suggestions for appropriate adjustment of relevant policy programs.;